Program Pendidikan Vokasional untuk Pengembangan Produk Olahan Pertanian Singkong di Komunitas Kelompok Tani Surabaya Baru, Lampung Tengah - Ihsan Mustofa; Suci Amalia; Akmal Attamimi (Institut Agama Islam Ma’arif NU (IAIMNU) Metro Lampung, 2021)
This community service program aimed to enhance the capacity of cassava farming communities in Surabaya Baru, Central Lampung, through vocational education focused on the development of value-added cassava-based products. Cassava, a staple crop in the region, has long been sold primarily in raw form, resulting in limited income and low market competitiveness for farmers. The implemented program utilized a participatory and hands-on training model covering technical skills in cassava processing (e.g., into mocaf flour, chips, cakes, and other innovative foods), food safety, business management, and digital marketing strategies. As a result, participants successfully produced a range of processed cassava products that met hygiene and packaging standards, significantly increasing their monthly income from IDR 3,500,000 to IDR 6,000,000. Moreover, the training fostered entrepreneurial mindsets and improved community solidarity, particularly among women. Challenges included limited access to modern processing equipment and the need for consistent product quality and marketing support. Nevertheless, this initiative demonstrated the transformative potential of vocational education in empowering rural communities through local agro-processing innovations, contributing to economic development, food security, and sustainable agribusiness practices. Keywords: agribusiness development, cassava processing, rural community empowerment, value-added products, vocational education.